Women Caring for Husbands Living with Parkinson’s Disease: A Phenomenological Study Protocol - White, Dawn R. (2022)
“Parkinson’s disease (PD) is an emerging pandemic caused by aging, longevity, and industrialization. Most people diagnosed with PD initially experience mild symptoms, but over time the symptoms become debilitating. Given their intensive care requirement, most married people living with PD receive care from their spouses; most are female caregivers. Because caregiving is hard work with long hours, caregivers experience stress, fatigue, and depression, often leading to exhaustion and burnout. The purpose of this descriptive phenomenological study is to understand the lived experience of women caregivers of husbands living with PD. As part of this study protocol, women caring at home for their husbands diagnosed with PD will be purposely recruited from the Colorado Parkinson Foundation. Semi-structured interviews will be conducted by Zoom© until data saturation is achieved. Colaizzi’s seven-step process will be used to analyze the data in Atlas.ti. Strategies have been incorporated into the study protocol to maximize trustworthiness and to insure methodological rigor. The study will be reported using recommendations from the Standards for Reporting Qualitative Research and the Consolidated Criteria for Reporting Qualitative Research. Findings from this study may guide intervention development to improve the caregiving experience and to inform clinical practice guidelines for health care professionals“